Juridical Analysis of the Effectiveness of Law Enforcement in Handling Nickel Mining Violations in North Maluku: Dispute Cases Between Companies and Affected Communities - Dewi, Ni Kadek Ari Pradnya (Indonesian Journal Publisher, 2025)
This study examines the effectiveness of the legal system in addressing nickel mining violations in North Maluku, particularly focusing on conflicts between mining companies and affected communities. Although regulations such as the Mineral and Coal Mining Law (UU Minerba) and the Environmental Protection and Management Law (UU PPLH) exist, law enforcement in practice remains ineffective. Disputes in Central Halmahera and East Halmahera highlight the negative impacts of mining activities, such as land encroachment and environmental degradation, which harm local communities. Moreover, companies are often not held accountable for the resulting damage, while communities opposing mining face criminalization. The study concludes that the existing legal system has not effectively protected the rights of communities and the environment from the negative impacts of mining activities. Weak law enforcement, lack of supervision, and the absence of corporate accountability are the main factors contributing to the imbalance in the protection of both communities and the environment. Therefore, improvements are needed in law enforcement, stricter monitoring of mining activities, and stronger protection of the rights of affected communities to create a fairer and more effective legal system.